2020
DOI: 10.3389/fcimb.2020.576263
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic DNA Sensors and CNS Responses to Viral Pathogens

Abstract: Viral central nervous system (CNS) infections can lead to life threatening encephalitis and long-term neurological deficits in survivors. Resident CNS cell types, such as astrocytes and microglia, are known to produce key inflammatory and antiviral mediators following infection with neurotropic DNA viruses. However, the mechanisms by which glia mediate such responses remain poorly understood. Recently, a class of intracellular pattern recognition receptors (PRRs), collectively known as DNA sensors, have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 197 publications
0
14
0
Order By: Relevance
“… 7–9 Microglia and astrocytes are resident glial cell types of the central nervous system (CNS), known to produce key inflammatory mediators following infection with pathogens. 10 , 11 It has been reported that microglia are the main source of inflammatory factors in the early stage of neuroinflammatory response, while astrocytes play an important role in the later stage of chronic inflammatory response. 12 There is increasing evidence that astrogliosis may lead to the developmental impairment of the CNS.…”
Section: Introductionmentioning
confidence: 99%
“… 7–9 Microglia and astrocytes are resident glial cell types of the central nervous system (CNS), known to produce key inflammatory mediators following infection with pathogens. 10 , 11 It has been reported that microglia are the main source of inflammatory factors in the early stage of neuroinflammatory response, while astrocytes play an important role in the later stage of chronic inflammatory response. 12 There is increasing evidence that astrogliosis may lead to the developmental impairment of the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the immune system, microglia are the sentinel cells of the brain and sensors for invading infectious agents [ 42 , 227 ]. In the context of viral infections, microglia orchestrate the local immune response [ 35 , 217 , 228 ].…”
Section: The Role Of Microglia In Viral Brain Infections Accelerating Brain Agingmentioning
confidence: 99%
“…For the most part, the brain's early innate immune response is largely sculpted by developmental requirements to help regulate neurogenesis; guide neural migration; winnow the surfeit of neurons and synapses initially produced; 16,17 and, after development, to contribute to synapse formation and elimination and promote synaptic plasticity 18 . Throughout life the brain's immune cells also protect from the relatively constant assault by bacteria, viruses, and parasites that, until recently, were common chronic human conditions 19–22 . The genetic programs available for the brain's innate immune response are designed and coordinated to succeed in these circumstances, not in response to brain injury caused by amyloid, tau, vascular damage, or myelin degeneration.…”
Section: General Considerations Regarding Innate Immune Biomarkersmentioning
confidence: 99%